Guidance Document: Global Pharmacoeconomic Model Adaption Strategies - Daniel Mullins, C; Onwudiwe, Nneka C; Branco de Araújo, Gabriela Tannus; Chen, Wen; Xuan, Jianwei; Tichopád, Aleš; Hu, Shanlian (Value in health regional issues, 2014)
OBJECTIVE: The purpose of this guidance was to assist in the adaptation of pharmacoeconomic models originally developed in one country and intended for use in another. The intent was to produce user-friendly recommendations and a checklist for adapting a global model to treat a specific disease state. This guidance will allow model developers to tailor existing models so that they are "locally applicable," while maintaining the scientific integrity of the original pharmacoeconomic model and will benefit formulary decision makers and other stakeholders involved in evaluating pharmacoeconomic studies. METHODS: A working group of experts from various countries participated in the Global Pharmacoeconomic Model Guidance development to discuss the adaptation of pharmacoeconomic models. A systematic review of studies adapting pharmacoeconomic models and translation across countries was conducted and recommendations were made for adaptation. The working group interviewed internal and external stakeholders to solicit best practices for model adaptation and developed a draft set of key principles and general recommendations for global adaptation. RESULTS: The working group provided a set of 16 recommendations for adapting pharmacoeconomic models for local decision makers. The recommendations span various aspects of estimating or modeling both the costs and effectiveness of pharmacoeconomic models as well as guidance for ensuring local acceptability. CONCLUSIONS: These recommendations and the related principles not only will provide pharmacoeconomic models that are meaningful to local decision makers but also will improve the consistency and credibility of pharmacoeconomic model adaptations. The guidance may also help those who will build the original models to design them with the flexibility to allow pharmacoeconomic model adaptations as described in this document.
Keywords: health technology assessment; cost-effectiveness analysis; pharmacoeconomic model